The Effect of Shear Rate on the Shear Strength of Saturated Coal-Measure Soil. Issue 1 (1st June 2022) - Chen, Kun; Zhang, Hong; Wu, Can; Liao, Liangjian; Zhu, Rui
Abstract: Coal-measure soil is easy to soften with water and has very poor stability. When encountering heavy rainfall, it loses strength and saturation failure occurs in a short period of time, which can easily cause instability and damage of coal-measure soil slopes, which is a great threat The traffic safety of the road. The shear strength of saturated coal-measure soil is affected by many factors. Since coal-measure soil is difficult to form samples after encountering water, the SLB-1A saturated soil triaxial tester is used to apply back pressure according to the principle of combining head saturation and back pressure saturation. Saturate. The UU test of 0.2mm/min, 0.4mm/min, 0.8mm/min, 1mm/min was applied to the sample with the confining pressure of 100kpa, 200kpa, 400kpa and 500kpa to study the resistance of the confining pressure and loading rate to the saturated coal measure soil. The effect of shear strength. Under the same shear rate, the shear strength increases with the increase of confining pressure. Under the same confining pressure and different shear rates, the shear strength changes very little and does not show regularity, because the coal-measure soil has poor structure.